Respuesta :
to solve the average rate of change, use the formula of the slope:
m = ( y2 - y1 ) / ( x2 - x1 )
but first we must solve the value of the function when x = 3
f(3) = - log ( 4 * 3 ) + 5
f (3) = 3.92
solve the function when x = 8
f(8) = - log ( 4 * 8) + 5
f(8) = 3.49
so the average rate of change
m = ( 3.49 - 3.92 ) / ( 8 - 3)
m = - 0.09
m = ( y2 - y1 ) / ( x2 - x1 )
but first we must solve the value of the function when x = 3
f(3) = - log ( 4 * 3 ) + 5
f (3) = 3.92
solve the function when x = 8
f(8) = - log ( 4 * 8) + 5
f(8) = 3.49
so the average rate of change
m = ( 3.49 - 3.92 ) / ( 8 - 3)
m = - 0.09